Biochanin A Regulates Key Steps of Inflammation Resolution in a Model of Antigen-Induced Arthritis via GPR30/PKA-Dependent Mechanism - Felix, Franciel Batista; Vago, Juliana Priscila; Fernandes, Débora de Oliveira; Martins, Débora Gonzaga; Moreira, Isabella Zaidan; Gonçalves, William Antonio; Costa, Walyson Coelho; Araújo, Jessica Maria Dantas; Queiroz-Junior, Celso Martins; Campolina-Silva, Gabriel Henrique; Soriani, Frederico Marianetti; Sousa, Lirlândia Pires; et al. (Frontiers in Pharmacology, 2021)
Biochanin A (BCA) is a natural organic compound of the class of phytochemicals known as flavonoids and isoflavone subclass predominantly found in red clover (Trifolium pratense). It has anti-inflammatory activity and some pro-resolving actions, such as neutrophil apoptosis. However, the effect of BCA in the resolution of inflammation is still poorly understood. In this study, we investigated the effects of BCA on the neutrophilic inflammatory response and its resolution in a model of antigen-induced arthritis. Male wild-type BALB/c mice were treated with BCA at the peak of the inflammatory process (12 h). BCA decreased the accumulation of migrated neutrophils, and this effect was associated with reduction of myeloperoxidase activity, IL-1β and CXCL1 levels, and the histological score in periarticular tissues. Joint dysfunction, as seen by mechanical hypernociception, was improved by treatment with BCA. The resolution interval (Ri) was also quantified, defining profiles of acute inflammatory parameters that include the amplitude and duration of the inflammatory response monitored by the neutrophil infiltration. BCA treatment shortened Ri from ∼23 h observed in vehicle-treated mice to ∼5.5 h, associated with an increase in apoptotic events and efferocytosis, both key steps for the resolution of inflammation. These effects of BCA were prevented by H89, an inhibitor of protein kinase A (PKA) and G15, a selective G protein–coupled receptor 30 (GPR30) antagonist. In line with the in vivo data, BCA also increased the efferocytic ability of murine bone marrow–derived macrophages. Collectively, these data indicate for the first time that BCA resolves neutrophilic inflammation acting in key steps of the resolution of inflammation, requiring activation of GPR30 and via stimulation of cAMP-dependent signaling.